Environmental & architectural phenomenology. Vol. 4, issue 2 - (:unkn) unknown (Kansas State University. Architecture Department, 1993)
Vol. 4, No. 2, Spring 1993 (includes “items of interest,” "citations received,” book review of Gerald L. Pocius' A Place to Belong, essays by Herb Childress & Gary Coates, and commentary of Bill Hillier's "Space Syntax").
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals